Prognosis of patients with severe burns based on plasma base excess and serum lactate level and comparison with ABSI - Alireza Sedaghat; Benyamin Fazli; arash peivandi; Farzaneh Fazeli; Bita Mirzaie Feyzabadi (Reviews in Clinical Medicine, 2022)
Background and Aim: This study was aimed to evaluate the prognosis of patients with severe burns by measuring the plasma base excess and serum lactate levels and comparing it with the ABSI scoring system as an important indicator in the resuscitation of burn patients.Methods: This prospective cohort study was performed on all patients hospitalized in the burn ward of the hospital. The demographic data and ABSI scoring of all patients were recorded. Patients' clinical information and routine tests, gasometry (for measuring plasma base excess) and serum lactate levels were measured at the time of admission, 12 hours, and 24 hours after admission.Results: A total of 311 burning patients were evaluated in this study. Mann-Whitney test showed a significant difference in the mean plasma BE1 (at the time of admission) and BE2 (24 hours after admission) between the patients who were discharged and the patients who died (P <0.001). The results indicated a difference in the process of lactate changes between two groups of patients in terms of intensity of ABSI(P <0.001). The multivariate logistic regression with the entry of BE and lactate at the time of admission and ABSI as predictive variables indicated a significant BE and ABSI.Conclusion: The results of this study confirmed that the plasma base excess can be used as a valuable tool in the monitoring of burn patients' resuscitation along with clinical criteria. On the other hand, the ABSI scoring system is still a valuable tool to predict the deaths of burn patients.